ANALISIS PENGARUH PENGGUNAAN MODAL KERJA DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PT. BANK RAKYAT INDONESIA, Tbk. - Rifdatul Anisah; Nurhayati Nurhayati (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine the effect of the use of working capital and Earning Per Share on stock prices at Bank Rakyat Indonesia (BRI) Tbk). The population in this study are financial reports for 2003-2021 which are listed on the Indonesia Stock Exchange (IDX). The sample technique used was purposive sampling so that the data obtained was 10 years from 2012-2021. The data used in this study is in the form of financial report data for 2012-2021. The data management method used is Multiple Linear Regression Analysis, which is a statistical method used to determine the relationship between the independent variable and the dependent variable, by testing the classical assumptions first. Tests were carried out to test whether the data in this study were normally distributed and did not have symptoms of multicollinearity and symptoms of heteroscedasticity. Multiple linear regression analysis method assessed from the t test, and F test and the coefficient of determination. The results of the study are: There is no significant effect partially between Working Capital on Stock Prices at PT. Bank Rakyat Indonesia, Tbk, there is a partially significant influence between Earning Per Share (EPS) on the Share Price at PT. Bank Rakyat Indonesia, Tbk. and there is a significant effect simultaneously between the Use of Working Capital and Earning Per Share (EPS) on Share Prices at PT. Bank Rakyat Indonesia, Tbk